?EVALUATION OF FIVE PAKISTANI WHEAT CULTIVARS FOR BISCUIT MAKING QUALITY - Hussain, Sarfraz; Ahmad, Munawar; Asif, Muhammad (Biological Sciences - PJSIR, 2000)
Five wheat cultivars Pak-81, Barani-83, Kohinoor-83, Faisalabad-85 and Chakwal-86 were evaluated for grain/flour character- istics and their biscuits making quality. Flours were subjected to proximate analyses, Farinograph absorption, alkaline water retention capacity (AWRC) and gluten content. The results showed a superior performance of Pak-81 for biscuit making compared with the remainder cultivars.